VALIDATION OF THE GUM METHOD USING MONTE CARLO METHOD TO EVALUATE THE MEASUREMENT UNCERTAINTY ASSOCIATED WITH BRINELL HARDNESS (REMUNOM, 2024)
The precise knowledge of measurement uncertainty is crucial for obtaining reliable results, being essential for traceability and regulatory control of measurement processes. The Guide to the Expression of Uncertainty in Measurement (GUM) is widely recognized by metrologists as the primary method for evaluating measurement uncertainty. However, due to identified limitations in the guide, the International Organization for Standardization (ISO) has developed a supplementary method for assessing measurement uncertainty based on the propagation of Probability Density Functions (PDF) through Monte Carlo Simulation (MCS). The supplement also presents a methodology for validating the GUM method based on coverage intervals provided by MCS. The aim of this study is to validate the GUM method using the Monte Carlo method in a Brinell hardness test. The results demonstrated that the methodology proposed by GUM was not approved in the Brinell hardness measurement process, for a tolerance limit of 0.5 HB. It was found from the results that the Monte Carlo method proved to be more robust and reliable for evaluating measurement uncertainty, suggesting its preference in similar situations.Keywords: Measurement Uncertainty. GUM Method. Monte Carlo Simulation.